Alcances, limites e antinomias de métodos e técnicas em cenários prospectivos - Samuel Alves Soares; Jéssica Gir\~ao Florêncio; Jonathan de Araujo de Assis; Kimberly Digolin; Raquel Gontijo; Ronaldo Montesano Canesin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The purpose of this paper is to present an overview of foresight methods and techniques, with the aim of updating the debate and highlighting the more recent approaches in the field. In revisiting these methods and techniques, we observed the need for a brief incursion in an epistemological discussion. On the one hand, we conclude that foresight studies lean toward a pragmatic standing, neglecting the epistemological rigor. This epistemological frailty can damage the field's legitimacy as an academic and scientific endeavor. On the other hand, we observe a clear revival of foresight, with new research centers around the world, which shows that futures studies are pivotal as a base for decision making processes and for the desire for change.
Keywords: C53; E17; C18; 330; futures studies; foresight; scenarios; forecasting